ERAS with or without supplemental artificial nutrition in open pancreatoduodenectomy for cancer. A multicenter, randomized, open labeled trial (RASTA study protocol) - Gianotti, Luca; Paiella, Salvatore; Frigerio, Isabella; Pecorelli, Nicolò; Capretti, Giovanni; Sandini, Marta; Bernasconi, Davide Paolo (Frontiers in Nutrition, 2023)
Purpose: The role of supplemental artificial nutrition in patients perioperatively treated according to enhanced recovery programs (ERAS) on surgery-related morbidity is not known. Therefore, there is a need of a clinical trials specifically designed to explore whether given a full nutritional requirement by parenteral feeding after surgery coupled with oral food “at will” compared to oral food “at will” alone, within an established ERAS program, could achieve a reduction of the morbidity burden. Materials and Analysis: RASTA will be a multicenter, randomized, parallel-arm, single-blind, phase III, superiority trial. The trial will be conducted in five Italian Institutions with proven experience in pancreatic surgery and already applying an established ERAS program. Adult patients (age ≥ 18 and < 90 years of age) candidate to elective open pancreatoduodenectomy (PD) for any periampullary or pancreatic cancer will be randomized to receive a full ERAS protocol that establishes oral food “at will” plus parenteral nutrition (PN) from postoperative day 1 to day 5 (treatment arm), or to ERAS protocol without PN (control arm). The primary endpoint of the trial is the complication burden within 90 days after the day of surgery. The complication burden will be assessed by the Comprehensive Complication Index, that incorporates all complications and their severity as defined by the Clavien-Dindo classification, and summarizes postoperative morbidity with a numerical scale ranging from 0 to 100 The H0 hypothesis tested is that he administration of a parenteral nutrition added to the ERAS protocol will not affect the CCI as compared to standard of care (ERAS). The H1 hypothesis is that the administration of a parenteral nutrition added to the ERAS protocol will positively affect the CCI as compared to standard of care (ERAS).The trial has been registered at ClinicalTrials.gov. (number: NCT04438447; date: 18/05/2020) Conclusion: This upcoming trial will permit to establish if early postoperative artificial nutritional support after PD may improve postoperative outcomes compared to oral nutrition alone within an established ERAS program.